IMPACT OF THE COVID-19 PANDEMIC ON CHRONIC PAIN MANAGEMENT: Interventional Pain during COVID-19 - Auyeung, Andrew; Wang , Hank; Pirvulescu , Iulia; Knezevic, Nebojsa Nick (Srpski medicinski časopis Lekarske komore, 2021)
Introduction The COVID-19 pandemic has generated considerable turmoil in the interventional pain management (IPM) community. Due to IPM being classified as “elective”, numerous pain practices across the United States were forced to close during the pandemic, leaving chronic pain patients untreated for indefinite periods and IPM physicians with increased stress and burnout. Results In response to these detrimental effects, various re-opening tools and techniques were created to facilitate a cautious resumption of in-person interventional pain practice. Due to their ability to minimize person-to-person contact, telehealth and pharmacotherapy played a more significant role in IPM during the pandemic, but their increased utilization has COVID-19 vaccine has also arisen as an issue of concern as well. also led to the exacerbation of substance abuse and the opioid epidemic. The interplay between steroid use and its immunosuppressive effects between COVID-19 infection and the Conclusion As practices begin to safely re-open throughout the United States, the effects felt by chronic pain patients during the pandemic must be emphasized and not ignored. This review emphasizes the struggles pain patients have had to face during the pandemic and the need to update and redefine regulations regarding interventional and chronic pain management.